Organization of internal audit mortgage transactions in subjects of its implementation - I.M. Vygivska; O.S. Gritsak (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article determines that the system of internal audit provides management personnel with reliable information for effective management of borrowed funds on the security (in a mortgagor) and financial activities of a mortgagee. The article deals with the organizational aspects of internal audit mortgage transactions (the loans payable to the mortgagor, the accounts receivable of the mortgagee, the subjects of mortgage). The study develops the organizational approach to the sequence of internal audit mortgage transactions in subjects of its implementation; the audit involves the selection of the following stages: before and at the moment of the mortgage contract making, in the performance of its conditions and after the completion of the contract. It is recommended to carry out the inventory of mortgage subjects (by its types) in the internal audit for the current control of the state, the number of mortgage subjects, their compliance to the mortgage agreements, identification of drawbacks and subsequent correction of accounting data.